2021
DOI: 10.1007/s11524-021-00584-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Maternal Health Care Among Immigrant Mothers in New York City, 2016–2018

Abstract: Immigrant women represent half of New York City (NYC) births, and some immigrant groups have elevated risk for poor maternal health outcomes. Disparities in health care utilization across the maternity care spectrum may contribute to differential maternal health outcomes. Data on immigrant maternal health utilization are under-explored in the literature. We conducted a cross-sectional analysis of the population-based NYC Pregnancy Risk Assessment Monitoring System survey, using 2016–2018 data linked to birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…19 Another recent study found that receipt of postpartum care was similar among immigrants and nonimmigrants in New York City, which covers all low-income immigrants. 20 The current study makes a substantial contribution to the existing literature by documenting a significant negative association between state public insurance policies that restrict eligibility by immigration status and receipt of postpartum care in a large sample of states with large immigrant populations.…”
Section: Discussionmentioning
confidence: 84%
“…19 Another recent study found that receipt of postpartum care was similar among immigrants and nonimmigrants in New York City, which covers all low-income immigrants. 20 The current study makes a substantial contribution to the existing literature by documenting a significant negative association between state public insurance policies that restrict eligibility by immigration status and receipt of postpartum care in a large sample of states with large immigrant populations.…”
Section: Discussionmentioning
confidence: 84%
“…The present study also assessed some maternity pathway‐related attributes that have been considered in a few previous studies 10–12 . High‐risk pregnancy, discomfort during pregnancy, delaying pregnancy examinations due to waiting, difficulty in accessing health services, and not having pregnancy examinations booked by health workers were risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous paper, we explored the main sociodemographic and delivery‐related features associated with a higher risk of pregnancy‐related UI using patient‐reported data collected longitudinally up to 6 months postpartum 9 . However, our previous work did not consider variables related to utilization patterns of maternity care pathways, which are crucial risk factors for maternal‐fetal comorbidities according to the literature 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Our finding that Medicaid exclusions appear to be detrimental to prenatal care use by women who are immigrants is a key link to emerging evidence on maternal health disadvantage faced by women who are immigrants. 29 The healthy immigrant effect is often found in research on reproductive health, such that immigrant women fared better than their US-born counterparts. 30 A 2018 report noted that, in fact, this health advantage erodes over time 31 and is not apparent in all immigrant groups.…”
Section: Discussionmentioning
confidence: 99%